Principles of personnel testing - Lawshe, C. H.; Balma, Michael J. (New York : McGraw-Hill, 1966)
It talks about mental/psychological testing.
Includes bibliographical footnotes and index.
occ 16/01/2019
Loans
Keywords: Ability; Employment tests